Natural compounds: new therapeutic approach for inhibition of Streptococcus mutans and dental caries - Kashi, Milad; Varseh, Mahdieh; Hariri, Yasaman; Chegini, Zahra; Shariati, Aref (Frontiers in Pharmacology, 2025)
Streptococcus mutans is recognized as one of the leading causes of dental caries, and biofilm formation by this bacterium plays a key role in dental plaque development and caries progression. Given the increasing resistance of bacteria to antibiotics and the adverse effects of some synthetic antimicrobials, the search for natural alternatives has received increasing attention. The recently published studies have demonstrated that natural compounds (NCs) such as curcumin, cinnamaldehyde, eugenol, thymol, carvacrol, epigallocatechin gallate, farnesol, catechin, inulin, menthol, apigenin, myricetin, oleanolic acid, and resveratrol, have notable antimicrobial properties and can effectively inhibit the growth of Streptococcus mutans. NCs can disrupt bacterial membrane integrity, leading to cell death, and possess the capability to inhibit acid production, which is a key factor in caries development. NCs can also interfere with bacterial adhesion to surfaces, including teeth. The attachment inhibition is achieved by decreasing the expression of adhesion factors such as gtfs, ftf, fruA, and gbpB. NCs can disrupt bacterial metabolism, inhibit biofilm formation, disperse existing biofilm, and interfere with quorum sensing and two-component signal transduction systems. Moreover, novel drug delivery platforms were used to enhance the bioavailability and stability of NCs. Studies have also indicated that NCs exhibit significant efficacy in combination therapies. Notably, curcumin has shown promising results in photodynamic therapy against S. mutans. The current review article analyzes the mechanisms of action of various NCs against S. mutans and investigates their potential as alternative or complementary therapeutic options for managing this bacterium and dental caries.